Strategi Pembelajaran Peningkatan Kemampuan Berpikir - Ramel Iftina Na'ifah; Raihani Salsabila; Gusmaneli Gusmaneli (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
In the era of globalization and rapid technological development, critical and creative thinking skills are important competencies that must be possessed by students to face real-world challenges. The learning strategy for improving thinking ability (SPPKB) is a learning approach that focuses on developing students' thinking skills through the analysis of facts or experiences and active problem solving. This learning model involves stages of onboarding, experience tracking, problem confrontation, inquiry, accommodation, and transfer to guide students to discover concepts independently and apply noble values such as honesty. In addition, this strategy demands active student involvement, increased motivation, and the use of technology and discussion methods to create a conducive learning environment. Although it has advantages in developing critical thinking skills, this strategy also faces challenges such as the need for sufficient time and the readiness of teachers and students in its implementation. With the right implementation, this learning strategy can increase students' thinking potential optimally and is relevant to the demands of modern education.